Allusive and interpretative typographic approach in prose book design - Pierro de Camargo, Iara (2016)
There are two approaches to the typographic choice for prose books: a functional one, that considers practical aspects like legibility, readability and neutrality (so that this choice doesn’t interfere in reading); and a more subjective and interpretative approach, that aims to establish semantic relations between text and its forms or historical and cultural questions regarding a typographical family. This approach can privilege aspects like allusion (allusive typography), atmosphere, etc. In this article, we present the argumentation of critics, designers and typographers about typographical choices of prose books that go beyond functional questions and three case studies in which designers Rudolph Ruzicka, Helen Gentry, Daniel Berkeley Updike, William A. Kittredge, Wilber H. “Chip” Schilling and Elaine Ramos used typography to establish semantical relations with the text.